هيكلة صكوك الإجارة السيادية في كوت ديفوار"Cote d'Ivoire" : دراسة فقهية تحليلية - سيلا، لانسينا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Sukuk has become one of the most important financial instruments and mechanisms in the field of economics and finances in terms of developing development projects especially for governments. However, this mechanism has not been recognized in the African market except in recent years by a few countries such as South Africa, Senegal, Nigeria, Gabon and Cote d'Ivoire in particully between 2013 and 2014. In this regard, the aim of this research is to discover the sovereign Ijara Sukuk issued by the State of Côte d'Ivoire and to examine the extent to which its structure complies with the criteria and rules of Shariah. In order to achieve this purpose, the study includes the information and data associated with the subject, using the indusive method to collect data and analyze them by discussing the jurisprudential opinions concerning some of the issues raised in the Bulletin. The research showed that the Islamic sovereign instruments have a bright future but it requires the presence of specialists, well-trained people in the field of Islamic-sukuk industry. In addition to that, it is believed that sukuk is a financial tool capable of stimulating the economy and improving infrastructure projects. Thus, the finding reveals that there are some shariah-based risks associated to this structure such as guaranteeing the investors'capital while recovering the assets at the end of the contract with the fixed price. Likewise, laying forth an incentive condition for those working for sukuk-oriented funds and the fall down of certain financial percentage. These are complex issues that impede the sukuk structures as legitimate in their formulation and design. This phenomenon may be due to the environment in which they were issued. Accordingly, the experience of this study may benefit all those who have a strong interest in the sukuk market in the waemu market in general and the Ivorian market in particular.